Does Intra-operative PRP Improve Patient Function & Complication Rates Following ACL Reconstruction With Meniscus Repair?. Issue 3 (27th March 2020) - Weldon, Matthew; Lowe, Walter R.; Lauck, Kyle; Kleihege, Jacquelyn; Warth, Ryan J.; Syed, Mohammad; Pontes, Ana C.; Hayes, Matthew; Bailey, Lane B.
Objectives: The frequent injury and compromised healing of intra-articular structures (i.e. cruciate ligaments and menisci) has led to an intense interest among surgeons and scientists for discovering new methods of enhancing the biological healing response of these tissues. Platelet-rich-plasma (PRP) contains various growth factors that positively effect biological healing, unfortunately few existing clinical studies are available to determine the risks and benefits of these therapies. Therefore, the purpose of this study was to determine the influence of intraoperative PRP on postoperative knee function and complications out to 2-years following ACL reconstruction with meniscus repair. Methods: A matched case-control study was conducted using a single surgeon database of 673 patients undergoing ACL reconstruction with concomitant meniscus repair (Figure 1) resulting in 324 patients [PRP (n = 162) vs matched-control (n = 162)] who met the study criteria. Patients were matched on age, gender, graft type, and meniscus tear size and location. The single assessment numeric evaluation (SANE) was administered at 2-years and served as the primary outcome measure. Secondary outcomes included the time to return-to-activity (mo), self-reported knee function [International Knee Disability Committee (IKDC)], objective functional testing (knee ROM, single-leg balance, single leg-hopping, agility testing), and postoperative complications (graft failure, infection, loss of motion, venous thrombosis, etc). Univariate models were used for between groups comparisons and alpha was set at .05 for all analyses. Results: There were no differences in SANE knee function scores between the PRP and matched-control groups at 2-years, respectively (91.6 ±11.2 vs 92.4 ±10.6, P = .599). Additionally, no differences were observed between groups for self-reported function (IKDC score; 87.6 ±13.3 vs 88.1 ±12.6, P = .952), objective functional testing (P > .05), and timing of return-to-activity (7.8 ±1.9 vs 8.0 ±1.9, P = .765). The PRP group demonstrated a higher rate of postoperative knee motion loss complications when compared to the control group (13.5% vs 4.9%, P < .001). No other differences were observed in postoperative complications (P > .05). Conclusion: The added use of intraoperative PRP did not improve self-reported knee function, objective functional testing, and timing of return-to-activity for patients undergoing ACL reconstruction with concomitant meniscus repair. Furthermore, the use of PRP may have negative consequences for regaining knee ROM after surgery. Based on these data, surgeons should cautiously consider the application of PRP when surgical planning for intra-articular injuries of the knee. :